Komitmen Organisasional Kerja Guru SMA Negeri 2 Sungai Raya Kabupaten Kubu raya - Fazarudin Fazarudin; Luhur Wicaksono; Halida Halida (Journal on Education, 2024)
This study aims to determine the work commitment of teachers at SMA Negeri 2 Sungai Raya. The research employs qualitative methods, with 5 subjects participating. Data collection methods include interviews, documentation, and observation. Data analysis is conducted through data reduction, data presentation, and verification. Data validity is checked through credibility, transferability, dependability, and confirmability tests. The study concludes that: 1) forms of teacher commitment include: teacher involvement in activities, constructive responses from teachers, teacher cooperation, concern for school development, teacher compliance, teacher loyalty, and choosing teaching as a lifelong career; 2) strategies to foster teacher work commitment include: commitment to core human values, clarification and communication of the organization's mission, ensuring organizational justice, creating a sense of community, and supporting teacher development; and 3) implications of teacher work commitment include: the impact of teacher commitment, information about obstacles faced, efforts made, and teachers implementing the curriculum with full responsibility. The conclusion of this research is that teacher work commitment has been effectively implemented. The implications of this research can serve as input for enhancing teacher work commitment.